Performance of 3D PPN against arbitrarily maneuvering target for homing phase - Li, Ke-Bo; Shin, Hyo-Sang; Tsourdos, Antonios; Tahk, Min-Jea (Institute of Electrical and Electronics Engineers (IEEE), 2020)
The performance analysis of the 3-D pure proportional navigation (PPN) guidance law was traditionally conducted by considering the cross-coupling effect of two independent 2-D PPN laws in the pitch and yaw planes. This could increase the complexity of the analysis and lead to conservative analysis results, especially when the target has maneuverability. To mitigate this issue, this article theoretically analyzes the performance of 3-D PPN directly on a rotating engagement plane using a Lyapunov-like approach. Considering practical issues, the analysis includes not only capturability, but also upper-bounds of heading error, line-of-sight rate, commanded acceleration, and closing speed. The analysis results obtained are also demonstrated by using numerical simulation examples. Compared to the previous studies providing the least conservative results, the analysis procedure is significantly simplified and the results are proven to be more practical and less conservative
Keywords: 3-D PPN; performance analysis; homing missile guidance Lyapunov-like approach; Arbitrarily maneuvering target